NILAI- NILAI TUTURAN EWA WUNA PADA MASYARAKAT MUNA - Arman . (Laboratorium Jurusan Antropologi, Fakultas Ilmu Budaya, Universitas Halu Oleo, 2016)
This study is about analyzing utterances and values ​​in Ewa Wuna on Muna society. The aims of this study are: (1) to analyze and to know the content of utterances about Ewa Wuna. (2) analyze the utterance values about Ewa Wuna. The methodology used is descriptive qualitative analysis techniques. Data was collected using the method; (1) literature searches, (2) in-depth and open interviews, (3) recording and documentation, and (4) observations involved. The research data are data obtained from informants in the form of Ewa Wuna utterances. The determination of informants in this study used the Snowball technique. The theory used in this research is the theory of value. From the analysis, aspects of Ewa Wuna utterances consist of: The name of stream, History of Ewa Wuna, Nature of Ewa Wuna, Genealogy Teacher-Student, Incidental of Study, Terms Being a Disciple, Sequence Learning In Ewa Wuna, and Values​​. In the analysis of values ​​in Ewa Wuna utterances contained some values ​​which are:(1) religious values;​, (2) philosophical values; (3) ethical values​; (4) aesthetic values, (5) politeness values, (6) solidarity values; (7) education values; (8) honesty values; (9) fortitude and patience values; and (10) sportivity values. Keywords: ewa wuna, utterances, value